2019
DOI: 10.22159/ijpps.2019v11i10.35248
|View full text |Cite
|
Sign up to set email alerts
|

IMMUNOMODULATORY, ANTICANCEROUS & ANTIOXIDANTACTIVITIES OF CYCLEA PELTATA (LAM.) HOOK.F. & THOMSON

Abstract: Introduction: Cyclea peltata (Lam.) Hook.f. & Thomson is an important plant listed in Ayurveda. The plants are used in digestive, diuretic and inflammatory disorders. Aim: The present study was to study the immunomodulatory, anticancerous and antioxidative properties of the fraction isolated from Cyclea peltata. Methods: The immunomodulatory activity was evaluated in lymphocytes and THP-1 macrophage cell lines. The anticancer activity of the fraction was determined by MTT assay. The antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Ascorbic acid showed the lowest IC 50 value and maximum scavenging activity in comparison to the extracts and fractions. Several reports indicated that the phenolic content of the plant extracts had the reducing power of bioactive compounds and associated antioxidant activity [14][15][16][17][18]. The reducing power (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Ascorbic acid showed the lowest IC 50 value and maximum scavenging activity in comparison to the extracts and fractions. Several reports indicated that the phenolic content of the plant extracts had the reducing power of bioactive compounds and associated antioxidant activity [14][15][16][17][18]. The reducing power (Fig.…”
Section: Discussionmentioning
confidence: 99%